IMPACT OF CONTINUOUS PATIENT COUNSELLING ON KNOWLEDGE, ATTITUDE, AND PRACTICES AND MEDICATION ADHERENCE OF DIABETIC PATIENTS ATTENDING OUTPATIENT PHARMACY SERVICES - E, RENUGA; SR, RAMAKRISHNAN; Rani N, Vanitha; P, THENNARASU; G, KANNAN (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The morbidity and morbidity associated with diabetes can be drastically reduced by the knowledge about diabetes mellitus and appropriate attitude toward the disease. A study was conducted to assess the level of knowledge, attitude, and practices (KAP) and medication adherence patterns of diabetic patients and effect of pharmacist‑led patient education on KAP and medication adherence patterns in these patients. Methods: 400 diabetic patients of either sex, aged above 18 years were divided randomly into two groups of 200 each as control and the intervention groups. At the baseline, patients in both the groups were assessed for KAP using KAP Questionnaire and medication adherence using Morisky Adherence Questionnaire. Patients in the intervention group were counseled both verbally and by distribution of a patient education leaflets at baseline and at three consecutive follow‑ups (1 st , 2 nd , and 3 months), and patients in the control group were counseled both verbally and by distribution of patient education leaflets at the baseline and then on the follow‑up after 3 months. Both the groups were assessed repeatedly for KAP and medication adherence using same questionnaires after each counseling sessions. The mean scores of KAP and medication adherence, and the fasting blood sugar levels (FBS) at the baseline and on the follow‑up for control and the intervention groups were analyzed statistically using independent sample t‑test and Mann–Whitney U‑test. rd Results: Of 200 patients in each group, 178 females and 22 males in the intervention group (mean age 57.80±9.878 years) and 179 females and 21 males in the control group (mean age 57.57±9.438 years). A statistically significant improvement in the mean KAP and adherence scores was observed from the baseline to the final follow‑up in both groups (p≤0.001). The increase in the KAP and medication adherence scores from baseline to the follow‑up in the intervention group was found to be significantly higher than the control group. There was a reduction in the mean FBS from baseline to the follow‑up in both the groups but a statistically significant higher reduction in the mean FBS was found in the intervention group from baseline to the final follow‑up when compared to the control group (p < 0.001). Conclusion: A better KAP of diabetic patients about their disease can improve the medication adherence behavior which in turn can improve clinical outcomes. The patient education should be a continuous process, and patients should be assessed at every subsequent visit for medication adherence to achieve better health outcome. Keywords: Diabetes, Adherence, Knowledge, attitude and practices, Patient education.